Pengaruh Media Aplikasi SAC dengan Pendekatan Joyful Learning terhadap Hasil Belajar Kognitif - Wahyuni, Dini Novia; Gusrayani, Diah; Nugraha, Rana Gustian (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Social studies is one of the most meaningful subjects for students, especially in elementary school. Therefore, supporting social studies learning with the use of technology-based learning media can have a positive influence on student learning outcomes. Various active and fun learning activities make using the SAC application media with a Joyful Learning approach the right alternative to improve students' cognitive learning outcomes. The aim of this research is to compare learning using the SAC application media with the Joyful Learning approach with conventional learning in improving students' cognitive learning outcomes. This research uses a quasi-experimental design with a non-equivalent group pattern. All sixth grade elementary school students in Pamulihan subdistrict became the research population, with Cicepatan State Elementary School selected as the sample. Class VI-A served as the control group, while class VI-B served as the experimental group. Data collection was carried out through cognitive tests, observing teacher performance, and observing student activities. Analysis of the results with a significance level of 0.05 revealed that both the use of the SAC application media with a fun learning approach and conventional methods succeeded in improving students' cognitive learning outcomes significantly. However, the use of SAC application media with a joyful learning approach is better than conventional learning in significantly improving students' cognitive learning outcomes.